"More meaningful to do it than just reading it:" rehearsing praxis among Mexican-American/Latinx pre-service teachers. Issue 4 (2nd October 2018) - Caldas, Blanca
ABSTRACT: This paper explores the potential use of drama-based pedagogical tools to prepare future bilingual teachers to respond to the need for advocacy inside and outside the classroom. Using their lived experiences and class material, 20 Mexican-American/Latinx bilingual pre-service teachers performed real-life narratives of conflict experienced by local seasoned bilingual teachers during a foundational class in a preparation program in the Southwest. Using Boal's Forum Theater, these reenactments provided bilingual pre-service teachers with a context to develop assertiveness and positionality as a means to co-construct emergent bilingual advocate-teacher identities. This paper uses critical ethnography and critical discourse analysis of video-recorded reenactments of bilingual pre-service teachers, as well as interviews and reflections.